Genetic gain prediction of the third recurrent selection cycle in a popcorn population - DOI: 10.4025/actasciagron.v30i5.3174 - Fabrício Santana Santos; Antonio Teixeira do Amaral Júnior; Silvério de Paiva Freitas Júnior; Ramon Macedo Rangel; Carlos Alberto Scapim; Freddy Mora (Acta Scientiarum. Agronomy, 2008)
Although Brazil has reduced its importation of popcorn grain in recent years, the availability of improved varieties is still rare. In order to improve a popcorn population and to estimate the prediction of genetic gains, the third cycle of intrapopulation recurrent selection was carried out. One hundred ninety two half-sib families were obtained from the second cycle of the UNB-2U population and tested in a randomized complete block design with two replications within sets in two locations. The presence of statistical significance for sets for grain yield, poorly husked ear and broken plants proved the efficiency and the necessity for the use of the hierarchical statistical model by sets. Except for the poorly husked ear, there was significance for families within sets for the other evaluated traits, showing that there was sufficient genetic variability for exploitation in future cycles. Although the heritability for popping expansion was higher than for grain yield, the predicted genetic gain for the latter was superior to popping expansion because of the higher magnitude of the genetic standard deviation for grain yield. It is expected that in the fifth recurrent cycle, the first popcorn variety with yellow grains may be released for Rio de Janeiro State.